Delta-like 4 - Notch signalling in angiogenesis and tumour biology - Shi, W (2007)
﻿ Notch signalling plays a key role in physiological development and tumourigenesis. The recent discovery and characterisation of Notch ligand Delta-like 4 (D114), which is predominantly expressed in endothelial cells, have underscored the role of Notch signalling in angiogenesis. This thesis investigates the regulation and function of D114-Notch signalling in angiogenesis and tumourigenesis. First, the D114-Notch pathway interacted with the cellular hypoxia-sensing pathway. In human umbilical vein endothelial cells (HUVECs), D114 overexpression repressed hypoxic induction, and the repression was mediated by Notch target gene Hey2. In the breast cancer cell line MCF7, hypoxia induced Notch target gene Hey1 and ligand Jagged2 via hypoxia inducible factor 1. The hypoxic induction of Hey1 was also dependent on Notch signalling. Second, D114 expression in HUVECs was up-regulated by several pathways. Notch signalling, activated by receptor overexpression, ligand stimulation or cell-cell contact, induced D114 expression. Treatment with vascular endothelial growth factor (VEGF) or hypoxia also induced D114 expression via Notch signalling. In addition, VEGF promoted Notch signalling and D114 expression in tumours. Third, D114 expression in HUVECs was up-regulated by co-culturing with cancer cells. B16 mouse melanoma cells and human breast cancer cell lines induced D114 expression in HUVECs via Notch signalling. B16 cells also induced D114 expression via soluble factors independent of Notch signalling. Finally, D114-Notch signalling regulated tumour growth in vivo. D114 overexpression in cancer cell lines activated Notch signalling in the stroma of xenograft tumours, and promoted the growth of human U87 (glioblastoma) and PC3 (prostate cancer) xenografts. In addition, D114-overexpressing U87 tumours were resistant to anti- VEGF treatment during later stages; however, they did respond to anti-Notch treatment. Altogether, the D114-Notch pathway is tightly regulated and plays an important role in physiological and tumour angiogenesis. Inhibiting this pathway may be a viable therapy for cancers resistant to VEGF inhibition.